2022
DOI: 10.33003/fjs-2022-0602-929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Causes and Consequences of Internal Displacement of Persons in Kaduna State

Abstract: The constraints faced by IDPs were many ranging from inadequate housing, poor medical health care, hazardous work, vulnerability of women and children to trafficking and sexual exploitation, discrimination based on ethnicity, religion, class or gender as well as break in social relations. The aim of the study was to assess the nature of internal displacement in terms of causes and consequences of the internally displaced persons in Kaduna State. The sample population was drawn from the three senatorial zones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In other words, scarcity can be worsened when people are forced to migrate into resource-constrained communities. Numerous studies on violent conflicts have found increasing social and communal conflict in the aftermath of shocks driven by disasters of natural origin, such as floods or droughts in Africa (Ducrotoy et al, 2016;A. Ibrahim et al, 2018;Kaimba et al, 2011).…”
Section: Related Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…In other words, scarcity can be worsened when people are forced to migrate into resource-constrained communities. Numerous studies on violent conflicts have found increasing social and communal conflict in the aftermath of shocks driven by disasters of natural origin, such as floods or droughts in Africa (Ducrotoy et al, 2016;A. Ibrahim et al, 2018;Kaimba et al, 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…A. Ibrahim et al (2018) employed a large amount of data obtained from pastoral households and argued for the need to enhance rural wellbeing so as to reduce the occurrences of social vices in Nigeria.…”
Section: Related Literaturementioning
confidence: 99%
See 3 more Smart Citations